การกำหนดกลยุทธ์ระดับธุรกิจและการประยุกต์ใช้ การประเมินแบบดุลยภาพสำหรับโรงงาน ผลิตบรรจุภัณฑ์ประเภทหลอดลามิเนท - ณัฐญ์ คุปตะวาทิน (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The aim of this thesis is to analyze the external environment and the internal environment and to formulate the business strategy for a manufacturer of laminated tube packaging. The company in the study is a laminated tube packaging factory located in Chachoengsao The research methodology consists of : (1) studying and collecting the information from the company, (2) analyzing the external environment and the internal environment by using strategic planning concept, (3) applying the Analytic Hierarchy Process which is a decision making tool to determine the best competitive strategy by Managing Director, Deputy Managing Director and Special Project division manager, and (4) applying the Balanced Scorecard concept to determine the important key performance indices at the level of business strategy and department strategy. The criteria for determining the best strategy consist of : 1.Objectives 2.Strengths 3.Weaknesses 4.Opportunities 5.Threats and 6.Key Success Factors. The generic competitive strategies consist of : 1.Overall Low-Cost Provider Strategy 2.Broad Differentiation Strategy 3.Best-Cost Provider Strategy 4.Focused Low-Cost Strategy 5.Focused Differentiation Strategy. The results indicate that the most important criterion for determining the best strategy is Key Success Factors and the best strategy for this company is Best-Cost Provider Strategy. After applying Balanced Scorecard, this company has 10 KPIs for factory division and 84 KPIs for 9 departments.